Iran’s Engagement in Syrian Conflic t. Causes and Consequences - Ożarowski, Rafał (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
Since the 2011, Iran is deeply engaged in Syrian war in order to support and keep President Bashar al-Assad in power. Firstly, Iran started with political and diplomatic support and later turned into military and economic assistance. At the moment, it is believed that Syria is financially sustained by Iran. The main reason that Iran has determined for wide-scale engagement was the existential need for maintaining and then expanding its own regional power influences in the Middle East. If Syrian regime collapsed, Iran would be dealt with a big dilemma and it would loss Syria as a key military and political ally. Thus, Iran would have cut off his transit route to supply weapons to Lebanon for Hezbollah, as these transports still go across Syrian territory. It would surely diminish the Iranian position in the Middle East. Preventing such a case, Iran has been determined to engage in the Syrian conflict to a great extent, which, as a consequence, is charged with heavy costs. Although there is no exact data of Iran’s expenses for the Syrian War, it is supposed that this is in the range of 6 billion USD to 35 billion USD. At the moment, it can be said that engagement in Syrian war was beneficial for Iran, mainly in political sphere, yet the full consequences of this involvement will only be known in many months.

Od 2011 roku Iran jest mocno zaangażowany w wojnę w Syrii, tak aby prezydent Baszar al- Asad utrzymał się u władzy. Początkowo Iran zaczął od wsparcia dyplomatycznego i szerokich działań politycznych na rzecz rządu syryjskiego. W późniejszym etapie jego wsparcie przyjęło formę militarną i finansową. Aktualnie można nawet przyjąć, że Syria jest dotowana przez Iran w szerokim zakresie. Głównym powodem, dla którego Iran jest tak zdeterminowany, aby wspierać reżim al-Asada jest egzystencjalna potrzeba utrzymania oddziaływania Iranu w regionie i tym samym swojej pozycji na Bliskim Wschodzie. Jeśli rządy B. al-Asada upadłyby, Iran stanąłby przed dużym wy¬zwaniem strategiczno-politycznym, a jego pozycja i znaczenie w regionie znacznie by osłabło. Syria do tej pory jest jedynym państwowym sojusznikiem polityczno-militarnym Iranu i brak „sy¬ryjskiego ogniwa” w polityce Iranu byłby również katastrofalny dla wsparcia militarnego, jakiego Iran udziela libańskiemu Hezbollahowi, które odbywa się przez terytorium Syrii. Aby uniknąć sytuacji, w której pozycja Iranu poprzez utratę Syrii jako sojusznika osłabnie, Iran podjął się udzielenia wsparcia, które generuje olbrzymie koszty. Szacuje się, że roczne wydatki Iranu na wojnę w Syrii i dotowanie państwa syryjskiego sięgają od 6 do 35 mld USD.
Udział Iranu w wojnie w Syrii. Przyczyny i następstwa
Keywords: Syria; Bashar al-Assad; Iran; Hezbollah; the so-called Islamic State; Syria; Baszar al-Assad; Iran; Hezbolla; tzw. Państwo Islamskie